2013
DOI: 10.1039/c3dt32417f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the extraction complexes of palladium(ii) with novel thiodiglycolamide and dithiodiglycolamide ligands by EXAFS and computational methods

Abstract: The structure of the extraction complexes of palladium(II) with novel ligands, namely, N,N,N',N'-tetra-(2-ethylhexyl) thiodiglycolamide (T(2EH)TDGA) and N,N,N',N'-tetra-(2-ethylhexyl) dithiodiglycolamide (DTDGA), have been determined by extended X-ray absorption fine structure spectroscopy (EXAFS). The interpretation of the EXAFS data is well supported by theoretical calculations of the complex geometry based on density functional theory (DFT). T(2EH)TDGA, having one thioetheric 'S' atom, forms a square planar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
6
12
0
Order By: Relevance
“…The trans congurations of palladium are in the majority as reported elsewhere [42][43][44] and are more energetically stable in view of the smaller steric hindrance. 45 Nevertheless, the cis conguration was obtained according to the results of X-ray crystallography. However, the powder pattern does not completely match with the XRD result of the sediment washed out of the [EMIm]NTF 2 with high levels of extracted complexes, which indicates that the trans conguration may also exist in the extracted complexes.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…The trans congurations of palladium are in the majority as reported elsewhere [42][43][44] and are more energetically stable in view of the smaller steric hindrance. 45 Nevertheless, the cis conguration was obtained according to the results of X-ray crystallography. However, the powder pattern does not completely match with the XRD result of the sediment washed out of the [EMIm]NTF 2 with high levels of extracted complexes, which indicates that the trans conguration may also exist in the extracted complexes.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…Indeed, if there is bonding between the metal and the carbamoyl group, then it should be reflected in the IR spectrum by showing a fre-quency difference (Δν) of 40-80 cm −1 for the carbamoyl group with respect to the free ligand. 11a The slight difference observed in the reported spectrum 10 has been explained recently as being due to the protonation of the carbamoyl group during contact with HNO 3 . 12 The observed Pd-O distance of 2.04 (±5%) Å in the EXAFS study may be due to the oxygen atom from water, nitrate or carbamoyl groups.…”
Section: Introductionmentioning
confidence: 87%
“…6 Recent studies using Extended X-ray Absorption Fine Structure (EXAFS) 9 and theoretical studies of a palladium nitrate compound with dithiodiglycolamide show that the ligand forms a 1 : 1 compound by bonding to the metal through both the thioether and carbamoyl groups in a tetradentate fashion (chelate binding mode). 10 However, there is no spectroscopic evidence provided to support that conclusion. Indeed, if there is bonding between the metal and the carbamoyl group, then it should be reflected in the IR spectrum by showing a fre-quency difference (Δν) of 40-80 cm −1 for the carbamoyl group with respect to the free ligand.…”
Section: Introductionmentioning
confidence: 97%
“…Among the sulfur-containing extractants, thiodiglycolamide (TDGA) extractants have exhibited both good selectivity and rapid extraction of Pd(II), and they are very durable in strongly acidic environments [15][16][17][18][19]. Some studies have used Fourier-transform infrared spectroscopy (FT-IR), extended X-ray absorption fine structure, and computational methods to investigate the extraction properties of TDGA-HNO 3 systems and have shown that TDGA molecules probably act as multidentate ligands through both the thioetheric sulfur atom and the carbonyl oxygen atom [20,21].…”
Section: Introductionmentioning
confidence: 99%